TECHNICAL ASPECTS OF ESTABLISHING BIOBRIQUETTE MANUFACTURING PLANT IN PENGABUAN DISTRICT, TANJUNG JABUNG BARAT REGENCY, JAMBI PROVINCE - Yulia, Ade (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Pengabuan District, Tanjung Jabung Barat Regency, Jambi Province, abundant biomass potential derived from coconut and areca nut processing residues, including coconut shells, coconut husks, and areca husks, which remain underutilized and potentially contribute to environmental pollution. This study aimed to evaluate the technical feasibility of establishing a biobriquette processing plant utilizing these agricultural residues as renewable energy sources. The research employed qualitative and quantitative approaches through observation, interviews, documentation, and literature review. Technical feasibility analysis covered raw material availability, production process design, production scheduling, mass balance analysis, industrial location selection using the weighted factor method, and factory layout planning using the Systematic Layout Planning (SLP) method. The results indicated that the availability of raw materials was sufficient to support continuous industrial-scale production. The proposed plant was estimated to produce 2,593 kg of biobriquettes per day or approximately 622,320 kg annually, with a production yield of 31.05%. The resulting biobriquettes satisfied the Indonesian National Standard (SNI), exhibiting a calorific value of 5324.7 cal/g, moisture content of 5.94%, ash content of 6.56%, and volatile matter content of 4.16%. Parit Pudin village was identified as the most feasible industrial location with the highest weighted score of 4.25. This study contributes to the development of renewable biomass energy and sustainable agroindustrial systems through the conversion of agricultural waste into environmentally friendly fuel products.